2006
DOI: 10.1042/bj20050726
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability enhancement and change in starch hydrolysis profile of the maltohexaose-forming amylase of Bacillus stearothermophilus US100 strain

Abstract: The implications of Asn315 and Val450 in the atypical starch hydrolysis profile of Bacillus stearothermophilus Amy (a-amylase) US100 have been suggested previously [Ben Ali, Mhiri, Mezghani and Bejar (2001) Enzyme Microb. Tech. 28, 537-542]. In order to confirm this hypothesis, three mutants were generated. Of these two have a single mutation, N315D or V450G, whereas the third contains both mutations. Analysis of the starch breakdown-profile of these three mutants, as well as of the wild-type, allowed us to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…The results demonstrated that the maximal thermostability was increased by ten degrees compared with the wild type BAA [92]. Similar studies by Mamdouh et al [94] reported that the amylase of Bacillus stearothermophilus US100 has an additional loop compared with the model of BLA. The deletion of two residues (Ile214 and Gly215) increased thermostability and reduced calcium requirements.…”
Section: Amylasesupporting
confidence: 53%
“…The results demonstrated that the maximal thermostability was increased by ten degrees compared with the wild type BAA [92]. Similar studies by Mamdouh et al [94] reported that the amylase of Bacillus stearothermophilus US100 has an additional loop compared with the model of BLA. The deletion of two residues (Ile214 and Gly215) increased thermostability and reduced calcium requirements.…”
Section: Amylasesupporting
confidence: 53%
“…Analysis of refined modeled structures of WT and mutated enzymes, which were simulated to mimic experimental conditions through atomistic molecular dynamic simulations at 27 and 80°C beside the biochemical analyses achievements, revealed that among manipulated phytases, the P9 and P12 mutants reached the desired thermostability and higher melting temperature simultaneously with catalytic efficiency improvement. Several recent studies have succeeded in combining thermostability with other enzyme properties such as hydrolysis profile [35] and substrate specificity [36]. In this study, we herein achieved improvement in both the thermostability and catalytic efficiency of mutants P9 and P12, suggesting that thermostability and catalytic efficiency may be fairly independent in the case of PhyA phytases, and both of them can be optimized at the same time.…”
Section: Discussionmentioning
confidence: 69%
“…Among the ␣-amylases, alkaline ␣-amylases are of special interest because they work under alkaline conditions encountered in the starch, detergent, and textile industries (2,3).…”
mentioning
confidence: 99%